2008
DOI: 10.3748/wjg.14.4705
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma in situ arising in a tubulovillous adenoma of the distal common bile duct: A case report

Abstract: Kim BS, Joo SH, Joo KR. Carcinoma in situ arising in a tubulovillous adenoma of the distal common bile duct: A case report.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 27 publications
1
26
0
Order By: Relevance
“…Patients with extrabiliary adenomas, on the other hand, have symptoms similar to cholangiocarcinoma with obstruction of biliary trees causing jaundice, fever, abdominal pain, biliary colic and pruritus 2. Our patient, however, was asymptomatic and the adenoma was detected incidentally.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Patients with extrabiliary adenomas, on the other hand, have symptoms similar to cholangiocarcinoma with obstruction of biliary trees causing jaundice, fever, abdominal pain, biliary colic and pruritus 2. Our patient, however, was asymptomatic and the adenoma was detected incidentally.…”
Section: Discussionmentioning
confidence: 60%
“…Meanwhile, adenomas of the extrahepatic biliary tree are incredibly sparse and intestinal histology is the commonest 5. Morphologically they are divided into papilloma, tubular adenoma, villous adenoma or tubulovillous adenoma 2 7. Rarely there can be fibromas and neuromas 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These have the same morphologic characteristics as intestinal villous/tubulovillous adenomas, and have a high risk of malignancy (6, 7). The first papillary (villous) adenoma of the common bile duct in the English literature has been reported by Saxe et al (9) and a total of 27 cases have been reported so far (3,8).…”
Section: Discussionmentioning
confidence: 99%
“…General symptoms are bile duct obstruction and jaundice. They may be confused with common bile duct stones and malignant tumors during pre-operative evaluation (3,4). Thus, unnecessary extensive surgical procedures can be applied in some cases.…”
Section: Introductionmentioning
confidence: 99%